The effects of social pensions on mortality among the extreme poor elderly - Olivera, Javier (2023)
We study the effects of Peru’s social pension programme Pension 65 on mortality. The programme provides pensions to people aged 65 and older who do not have other pensions and are extreme poor. The analysis relies on survey data obtained at the baseline and matched to mortality records of 2012-2019. We exploit the discontinuity around the welfare index used by the programme to determine eligibility, and estimate intention-totreat effects. We find that after seven years, the programme could reduce mortality among eligible people by about 11.4 percentage points, implying about one year more in life expectancy.